2017
DOI: 10.1186/s13018-017-0551-x
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical and histological effects of posterior cruciate ligament rupture on the medial tibial plateau

Abstract: BackgroundThe objective of this study was to investigate the biomechanical and histological effects of the posterior cruciate ligament (PCL) on the medial tibial plateau.MethodsA total of 12 cadaveric human knee specimens were collected and grouped as follows: the PCL intact group (n = 12), the anterolateral bundle rupture group (n = 6), the postmedial bundle rupture group (n = 6), and the PCL rupture group (n = 12). The strain on the anterior, middle, and posterior parts of the medial tibial plateau with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Rabbits were sacrificed 8 weeks after operation. Biopsies of the cartilage and bone were acquired from the tibia plateau, including the loading zone and the margin zone as far as possible ( Deng et al, 2017 ). Specimens were examined by Micro-CT. Articular cartilage was removed from the articular surface by sterile scalpel and was transferred to 4°C sterile DMEM (Hyclone, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbits were sacrificed 8 weeks after operation. Biopsies of the cartilage and bone were acquired from the tibia plateau, including the loading zone and the margin zone as far as possible ( Deng et al, 2017 ). Specimens were examined by Micro-CT. Articular cartilage was removed from the articular surface by sterile scalpel and was transferred to 4°C sterile DMEM (Hyclone, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The animals had free access to a normal diet and fresh tap water. Surgical transection of the PCL was performed randomly to one knee and PCL of the contralateral side was exposed but not transacted [16,17]. Specifically, the rabbits were anesthetized via the intraperitoneal administration of 3% sodium pentobarbital (0.03 mg/kg) and fixed on the operating table in a supine position.…”
Section: Methodsmentioning
confidence: 99%
“…The method used was the same as that in our previous study [15,16]. In short, rabbits were injected with 3% pentobarbital solution (0.03 mg/kg) through the ear vein.…”
Section: Model Preparationmentioning
confidence: 99%
“…Petrigliano et al [12] reported that 96.5% of PCL injuries were associated with other ligament injuries, including anterior cruciate ligament, lateral collateral ligament, or lateral stable structure injury. The biomechanical or histological effects of PCL rupture on the medial femoral condyle [13], the lateral femoral condyle [14], the medical tibial plateau [15], and the medical meniscus [16] have been studied by scholars. However, the effect of PCL rupture on the MCL is still lacking, and most of the existing studies focus on the ACL.…”
Section: Introductionmentioning
confidence: 99%